2015
DOI: 10.2147/ndt.s76292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged head-down bed rest on working memory

Abstract: BackgroundThe weightlessness caused by prolonged bed rest results in changes in cerebral circulation and thus, brain functions, which is of interest.MethodsWe investigated the effects of 45-day, −6° head-down bed rest, which stimulated microgravity, on working memory in 16 healthy male participants. The 2-back task was used to test the working memory variations on the 2nd day before bed rest (R−2); on the 11th (R11), 20th (R20), 32nd (R32), and 40th (R40) days of bed rest; and on the eighth day after bed rest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Finally, although the impairment in memory processes in people exposed to WBV are not clearly demonstrated, 32,33 several studies in mice have suggested that alterations of spatial navigation and memory could be induced by gravity changes. 34 This is supported by transcriptomic and proteomic analysis of brain in mice models, 22,35,36 and more recently in humans by magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although the impairment in memory processes in people exposed to WBV are not clearly demonstrated, 32,33 several studies in mice have suggested that alterations of spatial navigation and memory could be induced by gravity changes. 34 This is supported by transcriptomic and proteomic analysis of brain in mice models, 22,35,36 and more recently in humans by magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment caused by weightlessness has also been reported earlier. For example, participants' reaction time of working memory is significantly decreased in head-down bed rest (HDBR) ( 2 ). Pavy-Le et al ( 3 ) demonstrated that the balance between functional input and response output is disrupted, and HDBR detrimentally influence cognitive function under prolonged exposure to increased cephalic fluid distribution under simulated weightlessness ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Head-down bed rest in human and hindlimb suspension (HLS) are popularly used in animals to simulate microgravity on earth. Liu et al ( 2 ) reported that healthy young men ( n = 16) who participated in the two-back task exhibited significantly lower reaction time, suggesting that the prolonged HDBR may have a detrimental effect on working memory. HLS has been recognized as a cost-effective ground-based rodent model mimicking weightlessness in microgravity research ( 11 ), which is acceptable by the National Aeronautics and Space Administration.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of bed rest on cognitive function have been shown by different, studies to range from deterioration to improvement . Some reports indicated that 45 days SM has detrimental effects on executive functions . While other studies suggested that 8 days bed rest has no effect on cognitive performance .…”
Section: Introductionmentioning
confidence: 99%